Design of Work Facilities in Batik Production Using Anthropometry and Quality Function Deployment - Cici Finansia; Nuzila Putri Al-Bana; Grita Supriyanto Dewi; Arief Ikhwan Wicaksono (Universitas Suryakancana, 2026)
Batik is one of the creative economic sectors that plays an important role in supporting tourism and regional economic development in Yogyakarta City. One of the jumputan batik Small and Medium Enterprises (SMEs) located in Tahunan Village, Umbulharjo District, still relies on manual production processes with limited work facilities, resulting in musculoskeletal complaints caused by prolonged non-ergonomic working postures, particularly during the dyeing process. Preliminary studies and ergonomic risk assessments indicate that the dyeing process is classified as having a high risk of Musculoskeletal Disorders (MSDs) and therefore requires immediate improvement. This study aims to design an ergonomic worktable for the jumputan batik dyeing process to reduce the potential risk of MSDs based on user needs. The product design was conducted using the Quality Function Deployment (QFD) method to translate workers’ needs into technical specifications, supported by anthropometric data to determine ergonomic dimensions. The results produced an integrated worktable design that accommodates the dyeing, draining, and rinsing processes with more ergonomic sitting and standing working postures. The proposed worktable has a width of 53 cm, a sitting height of 52.18 cm, and a standing height of 69.27 cm, and is equipped with basins, filters, water taps, and a personal protective equipment rack. This ergonomic worktable design is expected to improve working comfort, reduce non-neutral postural loads, and minimize the risk of MSDs among jumputan batik SMEs workers.